CREATING A POSITIVE CLASSROOM CLIMATE TO ADDRESS DISCIPLINARY PROBLEMS IN SECONDARY SCHOOLS FOR QUALITY EDUCATION - Takpi, Samuel Orshio (Sokoto Educational Review, 2017)
This paper contests the act of subjecting students to corporal punishment by the schools’ administrators and teachers as a sure means of correcting disciplinary problems in the schools. It outlines effects of corporal punishment on students as; affecting their reasoning abilities, deter their social interaction and mutual understanding, hinders active participation in their academics activities etc. It also identifies some contributing factors behind prevalence of corporal punishment in schools such as; poverty, environment, temperament etc. This paper argues for; having classroom norms, making your class interesting, value of human dignity, understanding the meaning behind the behavior etc. as ingredients of positive classroom climate. It finally suggests that; positive disciplinary actions should be imbedded in teachers’ training program curriculum, remuneration of teachers should be increased to reduce their level of poverty, ministries of education at all levels should be organizing capacity building workshops in the most demanding areas of education such as; disciplinary management, class control, teaching methodology and resources etc. for teachers and schools’ administrators at least once in every two years.